Optimalisasi Kemampuan Membaca Teks Berita melalui Pengembangan Bahan Ajar Berbasis Aplikasi Lumio di Kelas XI Sekolah Menengah Atas Negeri 13 Medan - Amelia, Putri; Rita, Rita; Safina, Nila (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study aims to optimize students' ability to read news texts by developing teaching materials based on the Lumio application. The research employed a Research and Development (R&D) approach using the 4-D development model proposed by Thiagarajan (1974) as cited in Sugiyono (2020). The research population comprised 425 students at SMA Negeri 13 Medan, with a purposive sample of 36 students from class XI-11. Data were collected through questionnaires and expert validations, incorporating both qualitative feedback and quantitative scores. Validation results from material experts indicated feasibility with scores of 85% and 95%, while media experts yielded 98% and 92%. These results demonstrate that the developed teaching materials are highly suitable for classroom implementation. The product trial at SMA Negeri 13 Medan showed a teacher response rate of 94%. Student response data from the product trial reached 88.83%, categorized as "Very Effective." These findings suggest that the news text teaching materials assisted by the Lumio application are both highly feasible and effective for use in high school learning environments.